LEADERSHIP OF MULTICULTURAL LEARNING IN IMPROVING SOCIAL SOCIAL TEACHER COMPETENCY IN THE SURABAYA CITY, INDONESIA - Irsyad, Chamim Rosyidi; Sonhadji, Ahmad; Degeng, I Nyoman Sudana; Arifin, Imron (IJRDO- Journal of Educational Research, 2017)
The main objective of this research is to describe the leadership ofmulticultural learning in School Area (cluster school) in Surabaya City. Second,describe the social competence of teachers in the school area in the city of Surabaya.Third, describe the impact of multicultural learning leadership in improving theprofessional competence of teachers in the school area in the city of Surabaya. Thisstudy used a qualitative approach conducted on three School Area in the city ofSurabaya. Data collection techniques used include: (1) in-depth interviews; (2)participant observation; and (3) documentation study. The collected data is organizedand analyzed repeatedly. Data analysis was conducted in two stages, using individualcase study data which consisted of: (1) data reduction, (2) data presentation, and (3)conclusions (withdrawal/verification). The second stage, cross-case data analysisusing constant comparative method. To ensure the validity of the data, data validitytest, which consists of credibility, transferability, and confirmability. This studyyielded the following findings. First, the principal multicultural leadership leadershipof the School of Regions is: (1) religious; (2) visionary; (3) democracy; (4)transformational; (5) humanist; (6) innovative; (7) creative; (8) charismatic; And (9)collaborative, (10) inclusive. Second, the teacher's social competence in the SchoolArea in Surabaya City is: (1) inclusive, objective and non-discriminatory; (2)communicative, effective, empathetic, and polite; (3) adaptative on duty which hassocio-cultural diversity; And (4) communicative with the professional communityitself and other professions orally and in writing or other forms. Third, the impact ofmulticultural learning leadership in improving teacher competence in school area inSurabaya City is (1) to improve the quality of communication and teacher interactioneffectively with learners; (2) can improve the quality of communication andinteraction of teachers effectively with fellow educators and education personnel; (3)to improve the quality of communication and teacher interaction effectively withparents of learners and the surrounding community; and (4), can improve teacherperformance related to social competencies that are formulated, encouraged to beobjective and non-discriminatory; (5) improving communication quality effectivelyand empathy with fellow educators, education personnel, parents, and community sothat it can have further impact by producing a good and qualified learners output; (6)facilitate teachers to adapt in a duty that has socio-cultural diversity; (7) teachers areencouraged to actively communicate with the professional community themselves andother professions orally and in writing or other forms. This conclusion shows that theteacher can not work alone without regard to the environment and must be aware asan integral part of the academic community in which he serves and serves as well as with the outside community. (8) teachers accustomed to honed environmentalsensitivity and continuously discuss with colleagues in solving education and learningproblems.